Hepatic hydatid cyst hepatobronic transit in complicated a 10 year old boy - Anavitarte, Eduardo; Anavitarte, Eduardo; Arruti, Cesar; Torres, David (Cirugía del Uruguay, 1974)
A 10-year-old child presented a rare case of hydatid cyst in the liver entraining complication of hepatobronchial path. This case is described by the author, who includes a discussion of pathogeny, symptomatology and therapy of this disease